Legis Ratio of School Zonation System In Receiving New Students - Megantara Hanandyo Mulyono; Indriyanti Ayu Trisnawati; Pongga Adji Ardiansyah (Faculty of Law, Merdeka University Surabaya, Indonesia, 2021)
Education is a process or effort of every nation that is unbroken in nature at all levels of human life, in accordance with the development of society and culture that aims to achieve perfection and maturity in humans, so that with awareness and responsibility can face various problems of life. [1] It can be said that education is the key to the success of a nation, because education can improve the nation's Human Resources. Based on this the government issued regulations that regulate everything about education so that education in Indonesia is right on target and in line with expectations. One of them is the Minister of Education and Culture Regulation Number 20 of 2019 concerning Amendments to the Minister of Education and Culture Regulation Number 51 of 2018 concerning the Acceptance of New Students in Kindergartens, Elementary Schools, Middle Schools, High Schools, and Vocational High Schools . Wherein the Minister of Education and Culture Regulation No. 20 of 2019 is regulated regarding the school zoning system. in which regulates the school zoning system. The research method used in this study is to use normative juridical legal research methods, with 2 (two) approaches, namely: statute approach and conceptual approach. The formulation of the problem of this research is: What is the legis ratio in Minister of Education and Culture Regulation Number 20 Year 2019? The results of this study indicate that the legis ratio of the Minister of Education and Culture Regulation No. 20 of 2019 is that the acceptance of new students can be done objectively, accountably, transparently, and without discrimination. In addition, there is also an equitable distribution of quality education.